Photography Studio Information Management System - Mohathir, Nordini Emily; Arbaiy, Nureize (Applied Information Technology And Computer Science, 2025)
The photography and videography industry has grown rapidly due to digital technology and evolving consumer expectations. The web-based Photography Studio Information Management System was developed to address challenges for Hatta Awang Photography Studio to improve operational efficiency. Currently, the studio relies on manual methods to manage booking, which are time-consuming and prone to errors, impacting customer experience and creating inefficiencies for admin and staff in managing business data and communication. The system aims to streamline booking processes and enhance customer service. Developed using a prototyping methodology, the project leverages CSS, HTML, PHP, and MySQL for database management. Automation reduces the workload of staff and administrators, allowing them to manage studio services more effectively. Additionally, it provides customers with an intuitive platform to access business information, explore services, and make bookings conveniently, fostering customer satisfaction and loyalty.